2020
DOI: 10.2147/cmar.s227652
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA LEF1-AS1 Promotes Ovarian Cancer Development Through Interacting with miR-1285-3p</p>

Abstract: Background: Growing evidence indicates that long noncoding RNA (lncRNA) is a group of important regulator in cancer development. However, the correlation between lncRNA and ovarian cancer remains elusive. Here, we aimed to investigate the roles of LEF1-AS1 in ovarian cancer progression. Methods: LEF1-AS1 expression was analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Survival rate was analyzed by Kaplan-Meier method. Cell Counting Kit-8 (CCK8) and colony formation assays were used for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Nevertheless, the function of miR-1285-3p in OS remains uncertain. Previous studies have demonstrated that miR-1285-3p participates in the tumorigenesis of pancreatic cancer [ 31 ] and ovarian cancer [ 32 ]. The results of the present study indicated that miR-1285-3p was significantly decreased in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the function of miR-1285-3p in OS remains uncertain. Previous studies have demonstrated that miR-1285-3p participates in the tumorigenesis of pancreatic cancer [ 31 ] and ovarian cancer [ 32 ]. The results of the present study indicated that miR-1285-3p was significantly decreased in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that LEF1-AS1 knockdown significantly inhibits cell survival, proliferation and migration while enhancing cell apoptosis and inducing G0/G1 cell cycle arrest in oral squamous cell carcinoma, indicating a carcinogenic role of LEF1-AS1 in tumour progression [ 25 ]. Furthermore, LEF1-AS1 also has been proven to be positively correlated with lymph node metastasis and advanced stage during ovarian cancer progression, and enhanced LEF1-AS1 expression may predict a poor prognosis [ 26 ]. Nevertheless, the role of LEF1-AS1 and the underlying mechanism by which it functions in AIPC progression as remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that LEF1-AS1 knockdown inhibited cell survival, proliferation and migration, whereas enhanced cell apoptosis and induced G0/G1 cell cycle arrest in oral squamous cell carcinoma, hinting a cancerigenic role of LEF1-AS1 in tumour progression [25]. Furthermore, LEF1-AS1 also has been proven to be positively correlated with lymph node metastasis and advanced stage in ovarian cancer and Enhanced expression of LEF1-AS1 may predict a poor prognosis [26]. Nevertheless, the role of LEF1-AS1 and the underlying mechanism in AIPC progression remain unclear.…”
Section: Discussionmentioning
confidence: 99%